The Relationship Between Compliance of Jumantik Cadres in Larvae Eradication and the Incidence of Dengue Hemorrhagic Fever (DHF) - Ariantje Langi, Louisa; Ronald Tanggo, Christian (Rifa'Institute, 2025)
Introduction: Dengue hemorrhagic fever is a communicable disease that remains a major public health problem with high incidence and mortality. One prevention effort is mosquito nest eradication through the One House One Jumantik movement, which relies on the active role of Jumantik cadres. Objective: To determine the relationship between Jumantik cadre compliance in larval eradication activities and the incidence of dengue hemorrhagic fever in the community. Method: This was an analytical observational study with a cross sectional approach. The population consisted of all Jumantik cadres in the working area of the public health center, and samples were selected using purposive sampling. Data on cadre compliance were collected using a structured questionnaire, while dengue hemorrhagic fever cases were obtained from secondary surveillance data. Data were analyzed using the chi square test. Result and Discussion: The results showed a significant relationship between Jumantik cadre compliance and the incidence of dengue hemorrhagic fever (p < 0.05). Conclusions: Increased compliance of Jumantik cadres in implementing larval eradication activities can contribute to reducing the incidence of dengue hemorrhagic fever in the community.